Factors related to the satisfaction level of users in the outpatient clinic in hospital ii huánuco essalud welfare network, 2017 - Dámaso Mata, Bernardo Cristóbal (2018)
The objective was to determine the relationship between the waiting time for an appointment, the length of hospital stay, the orientation by non-medical staff and the explanation of the medical staff with the users' successful level in the outpatient clinic in the Hospital II Huánuco ESSALUD welfare network, 2017. The materials and study research method of cases and controls, the cases were with the highest successful level and the Controls with low level. For the calculation of the sample size of employment a proportion in exposed 0.80 and proportion in not exposed 0.60, error type I (0.05) and error type II (0.20). Convenience sampling. The successful level was evaluated with SERVQUAL. A data collection form was used, with trained personnel, who do not belong to the institution. It was approved by the research and ethics committees of Hospital II. Descriptive statistical analysis (proportions, medias, tables, graphs) and inferential (bivariate and multivariate) were performed. In the results, 310 participants were collected, the cases were 128 participants and the Controls were 182. In the bivariate inferential analysis, a significant association was found with Age (p = 0.024), Waiting time for a hospital appointment (p = 0.002), Services (p = 0.016), Receives explanation from the doctor (p = 0.000), Understands the doctor's explanation (p = 0.000). In the multivariate analysis, we found an association adjusted to the other variables with Service (p = 0.047, OR = 0.55 [IC95% 0.30-0.99]), Received doctor's explanation (p = 0.001, OR = 3, 62 [IC95% 1.74-7.54]), Understand the doctor's explanation (p=0,000; OR=5,73 [IC95% 3,02-10,86]). We conclude that the factors associated independently to the successful level in the users of the outpatient clinic was the Service where it was attended; receiving an explanation from the doctor and understanding the doctor's explanation.